Conservative management in case of placenta accreta followed by hysterectomy - Nagraj, Devina (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
With a rise in number of caesarean sections we are also seeing an increase in the adherent placenta that form a part of placenta accreta spectrum. Early identification and appropriate management and monitoring is very important in these patients as they can have hemorrhage that can cause significant maternal and fetal morbidity and mortality. This is a case of conservative management of a woman with placenta accreta spectrum, use of uterine artery balloon ligation to decrease the intra-operative blood loss, leaving placenta in situ, methotrexate therapy and follow up of the patient that ultimately led to hysterectomy. It highlights the importance of managing these women in adequately equipped center with the required expertise and intensive care support and multidisciplinary management to improve patient care leading to good maternal and fetal outcome.